Isolation and pan-genome analysis of Enterobacter hormaechei Z129, a ureolytic bacterium, from the rumen of dairy cow - Zhong, Huiyue; Zheng, Nan; Wang, Jiaqi; Zhao, Shengguo (Frontiers in Microbiology, 2023)
Urea is an important non-protein nitrogen source for ruminants. In the rumen, ureolytic bacteria play critical roles in urea-nitrogen metabolism, however, a few ureolytic strains have been isolated and genomically sequenced. The purpose of this study was to isolate a novel ureolytic bacterial strain from cattle rumen and characterize its genome and function. The ureolytic bacterium was isolated using an anaerobic medium with urea and phenol red as a screening indicator from the rumen fluid of dairy cattle. The genome of isolates was sequenced, assembled, annotated, and comparatively analyzed. A gram-positive ureolytic strain was isolated. Its genome had a length of 4.52 Mbp and predicted genes of 4223. The 16S rRNA gene and genome GTDB-Tk taxonomic annotation showed that it was a novel strain of Enterobacter hormaechei, and it was named E. hormaechei Z129. The pan-genome analysis showed that Z129 had the highest identity to E. hormaechei ATCC 49162 with a genome average nucleotide identity of 98.69% and possessed 238 unique genes. Strain Z129 was the first E. hormaechei strain isolated from the rumen as we know. The functional annotation of the Z129 genome showed genes related to urea metabolism, including urea transport (urtA-urtE), nickel ion transport (ureJ, tonB, nixA, exbB, exbD, and rcnA), urease activation (ureA-ureG) and ammonia assimilation (gdhA, glnA, glnB, glnE, glnL, glsA, gltB, and gltD) were present. Genes involved in carbohydrate metabolism were also present, including starch hydrolysis (amyE), cellulose hydrolysis (celB and bglX), xylose transport (xylF-xylH) and glycolysis (pgi, pgk, fbaA, eno, pfkA, gap, pyk, gpmL). Biochemical activity analysis showed that Z129 was positive for alkaline phosphatase, leucine arylamidase, acid phosphatase, naphthol-AS-BI-phosphohydrolase, α-glucosidase, β-glucosidase, and pyrrolidone arylaminase, and had the ability to use D-ribose, L-arabinose, and D-lactose. Urea-nitrogen hydrolysis rate of Z129 reached 55.37% at 48 h of incubation. Therefore, the isolated novel ureolytic strain E. hormaechei Z129 had diverse nitrogen and carbon metabolisms, and is a preferred model to study the urea hydrolysis mechanism in the rumen.